2014
DOI: 10.1504/ijsd.2014.065325
|View full text |Cite
|
Sign up to set email alerts
|

Towards integrating sustainable development in South African universities' accounting education

Abstract: This article attempts to depict a linkage between accounting education and sustainable development and how accounting education in South Africa may be fine-tuned to play an advocacy role toward sustainable development. The methodological approach is conceptually rooted in reviews coalesced with a suggested model of reform in accounting curricula. The article revisits the notion of sustainable development, and reviews the implication for and role of accounting education. Findings indicate that there is currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(54 reference statements)
0
6
0
1
Order By: Relevance
“…In fact, these results are consistent with the results of a large number of studies conducted in different countries, which provided evidence on the weakness of integrating sustainable development issues in accounting education because the response of accounting education is less than the growing interest in sustainability, which has resulted in university students' knowledge of sustainability has not been sufficiently developed. These studies included, for example, Botes et al (2014) in New Zealand, Ngwakwa (2014) in South Africa, Fernandez et al (2015) in Spain, Bouliame et al (2018) in France, Ahmed (2019) in and Gomes et al (2021) in Portugal.…”
Section: Descriptive Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, these results are consistent with the results of a large number of studies conducted in different countries, which provided evidence on the weakness of integrating sustainable development issues in accounting education because the response of accounting education is less than the growing interest in sustainability, which has resulted in university students' knowledge of sustainability has not been sufficiently developed. These studies included, for example, Botes et al (2014) in New Zealand, Ngwakwa (2014) in South Africa, Fernandez et al (2015) in Spain, Bouliame et al (2018) in France, Ahmed (2019) in and Gomes et al (2021) in Portugal.…”
Section: Descriptive Analysis and Resultsmentioning
confidence: 99%
“…Most of the students expressed that education for sustainable development is a good thing and they support the sustainable business learning experience offered at their university. Ngwakwe (2014) examined the relationship between accounting education and sustainable development and how accounting education in South Africa can play a role in supporting sustainable development. His findings indicated that there is currently a gap between contemporary demand for social and environmental sustainability and the current position of accounting education.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…No entanto, alguns autores alertam que o desenvolvimento sustentável no ensino superior ainda está longe de ser integrado de forma adequada (Berchin et al, 2017;Jorge et al, 2015;Lee, Barker, & Mouasher, 2013;Lozano et al, 2013;Ngwakwe, 2014), sendo um dos pontos mais ressaltados, a integração mais abrangente da sustentabilidade, em vez de apenas um "complemento" para as práticas existentes (Fadeeva & Mochizuki, 2010).…”
Section: O Papel Das Instituições De Ensino Superiorunclassified
“…With a growing interest in sustainability, an increasing number of colleges and universities want to equip students with skills and insights to help society become more sustainable in their future professional careers. However, there has not been major progress in broadening accounting's boundaries in a sustainability context, and the efforts to reform outdated accounting education has been disappointing [8,12,13]. Currently, only very few accounting programs focus on sustainability issues, including the Bachelor of Accounting and Sustainable Business at the University of Southern Queensland, and the Masters in Sustainable Finance and Accounting at the University of Sussex.…”
Section: Introductionmentioning
confidence: 99%